(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This investigation adresses the importance of developing meaningfully the criminal jurisdiction specialized in young offenders, to ensure one the pillars of the human right of access to justice for the mentioned population, in order to assure the respect and implementation of all the general and specific standards established by national and international legal instruments that support due diligence in the context of a criminal investigation. With this understanding, some of the guiding principles are: the right not to be discriminated against, the equality before the law, the right to be judged by specialized justice workers, the presumption of innocence, the lawfulness and judicial security, the best interest of the child/adolescent, the progressive autonomy and the right to be heard, among others. To make these rights effective, Paraguay needs to continue with the suitability of its home legislation, but based on the enforced International Conventions, as a State Party of the Convention on the Rights of the Child and other international legal instruments related to the Rights of the Child. Furthermore, it is important to adopt mechanisms to assure the full implementation of the juvenile justice standards, by justice workers.